SISTEM ANALISIS BUTIR SOAL PADA CBT DENGAN METODE TEORI RESPON BUTIR - Wahyuni Wahyuni; Muhammad Fahmi (Jurnal Ilmiah Matrik, 2021)
Analysis of the quality of the items is carried out so that the questions made actually consist of quality items in order to measure learning outcomes. Currently, there are still many teachers who have not analyzed the questions they made because they think that analyzing the questions takes a long time and takes a lot of energy. As a result, many items used cannot produce correct data about student learning outcomes. Therefore, a Question Item Analysis System was made using the Website-based Item Response Theory method to determine the quality of the items presented. In this study, a website-based item analysis system was developed using the item response theory method with a 3PL approach model. This system is made one package with CBT. Responses from participants to analyze the items are obtained automatically when participants take the CBT test